TIPOLOGI FILSAFAT PENDIDIKAN ISLAM DAN IMPLEMENTASINYA DALAM PENGEMBANGAN KURIKULUM - Achmad, Bani (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2014)
Philosophy with its orderly ways of working, universal, and radical that husks, analyze is something exhaustively, apparently so relevant with all problematics of lives and man life and can become back paste among various kind was disciplined by knowledge that separatedly its bearing one by another one. Philosophy thus seemingly was effloresce and changed of mother of science as analysis and solving about problem philosophical of world scholarship and real man life (philosophical analysis). Turn on corresponds to study on this therefore, philosophy has implication on developmental education curriculum comprises at in itÃ¢â¬â¢s Islamic education. Base tipologi education philosophy that be compared with tipologi Islam thinking, therefore Islamic education curriculum gets to be developed by philosophy perspective.